Glucocorticoid receptors in oligodendrocyte precursor cells regulate hippocampal network plasticity and stress-induced behavior in mice - Lorenzo Mattioni; Giulia Poggi; Celine Gallagher; Katrin Becker; Linh Le; Maja Papic; Jasmin Engbers; Maija-Kreetta Koskinen; Ali Abdollahzadeh; David P. Herzog; Leonardo Nardi; Andrea Conrad; et al. (Proceedings of the National Academy of Sciences, 2026)
Glucocorticoid receptors (GRs) are key mediators of how the stress hormone glucocorticoids (GCs) shape postnatal brain development and adaptive plasticity. Because GC signaling is critical during this period, postnatal GC concentrations are tightly regulated in the brain, whereas excessive levels of circulating GCs can disrupt developmental trajectories and increase the risk of psychiatric disorders later in life. GR function influences multiple neural cell types, but its cell-specific roles, particularly early in development, remain poorly understood. Oligodendrocyte precursor cells (OPCs), which generate myelinating oligodendrocytes and actively modulate neuronal networks, express GRs and can therefore respond to fluctuations in GC levels. Although excessive GC exposure during early life adversity has been linked to changes in OPC development, the physiological role of GR signaling specifically within OPCs remains unclear. To address this, we conditionally deleted GRs in postnatal OPCs in mice to investigate the role of physiological GC signaling in OPC proliferation and maturation, as well as in neuronal network activity and behavior. This deletion resulted in reduced oligodendrocyte and myelinated axon density in the hippocampus, sex-specific alterations in hippocampal activity and long-term potentiation following acute challenge, and impairments in memory formation in adulthood. Our findings reveal an OPC-specific role for GRs and suggest that physiological GR activity in the oligodendrocyte lineage contributes to normal hippocampal plasticity, learning, and memory.